Anthropogenic legacies shaping the present composition of demarcation trees in a temperate upland field landscape in Japan - Tokuoka Yoshinori; Kimura Kenichiro; Oka Mitsunori (BMC, 2022)
Abstract Background Isolated trees are often planted in agricultural landscapes around the world, but their planting background often remains unclear. In this study, we examined the history of demarcation trees in Ibaraki Prefecture in eastern Japan by using land dispute records mainly from the early modern period (from 1600 to 1868), the Rapid Survey Map (RSM) drawn in the late nineteenth century, demarcation tree records from 2011, and interviews of the local residents. Methods We reviewed 39 documents on land disputes to examine the temporal and spatial usage of demarcation tree species in the early modern period. The association between the present distribution of 1486 individuals of six demarcation tree species and past land use in the RSM were analyzed with Fisher's exact test and residual analysis. In addition, we conducted interviews with 48 farmers, most of whom were over 60 years old. Results The demarcation plants in vast communal lands and village boundaries in the early modern period were mostly visually prominent tall trees, usually pines. In contrast, smaller trees were planted for demarcation in small-scale areas of forests and farmlands. Although Pourthiaea villosa (Thunb.) DC. Has been planted since the mid-eighteenth century, its planting seems to have accelerated as communal forests were divided mainly in the Meiji period (from 1868 to 1912). The present dominant state of Deutzia crenata Siebold et Zucc. in older farmlands and its ritual use, history of upland field development in the Kanto region, and ancient demarcation use in central Japan indicate its original use may date back to the medieval (from 1185 to 1600) or ancient ritsuryo period (from the seventh century to 1185). Tea (Camellia sinensis (L.) Kuntze) and mulberry (Morus spp.) individuals were considered as early modern or modern crop remnants. Results from the map-based analysis and interviews clarified the recent increase in the use of Euonymus japonicus Thunb. and Celtis sinensis Pers. for demarcation. Conclusions Chronologically dynamic anthropogenic legacies have shaped the present agricultural landscape with different demarcation tree species. A better understanding of the dynamic transformation of vegetation under human influence adds to the historical heritage value of the landscape and should motivate its conservation.